An An Analysis of Directive Speech Acts Used in “The Blind Side” Movie by Michael Lewis - Ladita, Safira; Jazadi, Iwan (Journal of Language and Literature Studies, 2024)
It is fascinating to conduct a study on the directive speech acts because it is so common in everyday life, especially in conversation. Sometimes communication fails simply because the hearer does not understand what the speaker is saying. As a result, the intended message could not be sent effectively and several differences were found in the use of speech acts. The focus of this research was to analyze the use of directive speech acts in the movie “The Blind Side” by Michael Lewis. The research aimed to (1) identify the types of directive speech acts used by the characters in the movie “The Blind Side” by Michael Lewis, and (2) determine the factors influencing the use of each type of directive speech act by the characters. This research was qualitative, employing descriptive techniques. The data sources included primary sources such as video and script, and secondary sources such as articles, journals, and relevant studies. The researchers utilized documentation, observation, and literature study techniques in data collection to draw conclusions after analysis. Searle’s and Hymes’ theory are used to analyze the data. From the observations and literature study, the results obtained were (1) five types of directive speech acts were found to be used by the characters in the movie, namely command, request, invitation, prohibition, and suggestion, and (2) there were factors influencing the use of each type of directive speech act by the characters, including gender, age, race/skin color, and social status/occupation, with race/skin color being the most dominant factor influencing them.